STUDIO MEDIA VISUAL DAN SINEMA RUANG LUAR MELAWAI - Maudy Maharani; Lina Purnama (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2020)
The media is one among many other factors, that is responsible for the dissemination of information amidst modern society. The Melawai Visual Media Community Studio and Open- Cinema project is created as a response towards the multicultural phenomenon caused by high plurarity rate of residents coming from different regions, locally or internationally. It aims to restore local values that starts to becoming insignificant among rapid globalization that is happening in the area. In addition, it also plays a role in strengthening relations between community-based social circles through efforts to foster a sense of pride towards local creative products. Synergized with M- Bloc Space which is a collaboration between PERURI and local creative industries intended to provide a space for creative-based community as a meeting point that is intergrated with Sisingamangaraja MRT Stop and Blok-M MRT Stop, Visual Media Community Studio and Open-Cinema project helps to upgrade the quality of the residents socially, economically and culturally through Creation and Appreciation program. The concept of Creation and Apreciation is the sole base of reference to determine the placement of programs on site, as the Open- Cinema (apreciation) placed in the center, supported by Pre-productions, Productions, and Post- Productions programs (creation) which revolves around it. The Street-sport zone program is also presented as a neutral space that is expected to attract new visitors outside visual media community, also to contribute in supporting the creativity programs through stimulation of mind through physical movement. The method used for this project’s design is examining several important contextual parameters around the area (cultural, nature, urban, and buildings’ form) as to produce a form that is explorative but still possess the soul of Colonial Architecture used in the remain buldings of PERURI and M-Bloc Space through the use of vertical elements and the minimalism of material chosen for the building. AbstrakMedia merupakan salah satu unsur yang bertanggung jawab atas penyebaran informasi ditengah masyarakat modern. Proyek Studio Media Visual dan Sinema Ruang Luar Melawai merupakan respon atas fenomena multikultur yang disebabkan oleh pluraritas masyarakat yang tinggi di kawasan tersebut. Tujuannya adalah untuk mengembalikan kembali nilai-nilai lokal yang kabur ditengah derasnya arus pengaruh dari budaya asing. Selain itu, proyek juga berperan sebagai pemererat hubungan antar masyarakat Melawai dalam asas komunitas melalui usaha dalam menumbuhkan rasa kebanggaan tidak hanya terhadap karya asing namun juga karya anak bangsa, melalui konsep dan program yang ditawarkan. Dengan sinergi terhadap proyek M-Bloc space yang merupakan kerja sama antara PERURI dengan badan swasta guna menciptakan ruang kreatif sebagai meeting point yang terintegrasi dengan Halte MRT Sisingamangaraja dan Halte MRT Blok-M, proyek Studio Media Visual dan Sinema Ruang Luar ikut berkontribusi dalam meningkatkan kualitas masyrakat secara sosial, ekonomi maupun budaya melalui kegiatan kreasi dan apresiasi karya. Konsep kreasi dan apreasiasi juga dijadikan sebagai dasar atas program dan penempatan ruang, dimana Sinema Ruang Luar berperan sebagai pusat (apresiasi) dan studio pre-produksi, produksi, dan pos- produksi yang mengegelilinginya. Program street- sport zone juga dihadirkan sebagai ruang netral yang diharapkan dapat menarik pengunjung baru diluar komunitas dengan minat yang sama, juga memicu kreatifitas komunitas melalui stimulasi pikiran melalui gerak fisik. Metode yang digunakan merupakan pendekatan kontekstual yang mengkaji empat parameter kontekstual (budaya, alam, urban, dan fisik bangunan) yang menghasilkan bentuk yang eksploratif namun tetap menyisikpkan unsur- unsur kolonial yang merupakan wujud bangunan dari kompleks Eks- PERURI dan M-Bloc Space.